2017
DOI: 10.1007/s10995-017-2306-z
|View full text |Cite
|
Sign up to set email alerts
|

Mother and Adolescent Eating in the Context of Food Insecurity: Findings from Urban Public Housing

Abstract: Introduction Anecdotal evidence suggests that parents protect their children from food insecurity and its effects, but few studies have concurrently assessed food insecurity among youth and parents. The purpose of this study was to examine food insecurity and eating behaviors among an urban sample of mother-adolescent dyads. Methods Mother-adolescent dyads (n = 55) were from six public housing sites in Phoenix, Arizona who completed surveys during 2014. Multivariate mixed linear and logistic regression models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Most of the studies identified were from North America (91 from the USA and 10 from Canada), 21,23,27,42,43,45,46,68,75,76 five were from the UK, 19,[30][31][32]59 one was from Ireland, 106 one was from Australia 54 and one was from New Zealand. 122 Of the 109 studies included in the review, 100 were quantitative studies, 9,12,[18][19][20][21][22][23][24][26][27][28][29]33,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][56]…”
Section: Chapter 3 Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most of the studies identified were from North America (91 from the USA and 10 from Canada), 21,23,27,42,43,45,46,68,75,76 five were from the UK, 19,[30][31][32]59 one was from Ireland, 106 one was from Australia 54 and one was from New Zealand. 122 Of the 109 studies included in the review, 100 were quantitative studies, 9,12,[18][19][20][21][22][23][24][26][27][28][29]33,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][56]…”
Section: Chapter 3 Resultsmentioning
confidence: 99%
“…122 Of the 109 studies included in the review, 100 were quantitative studies, 9,12,[18][19][20][21][22][23][24][26][27][28][29]33,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][56][57][58]60,61,[63][64][65][66][67][68][69][70][71][72][73][74][75][76][7...…”
Section: Chapter 3 Resultsmentioning
confidence: 99%
See 3 more Smart Citations